Associations between Child Disabilities and Caregiver Discipline and Violence in Low- and Middle-Income Countries - Hendricks, Charlene (2013)
Using nationally representative samples of 45,964 2- to 9-year-old children and their primary caregivers in 17 developing countries, we sought to understand relations between children’s cognitive, language, sensory, and motor disabilities and caregivers’ use of discipline and violence. Primary caregivers reported on their child’s disabilities and whether they or anyone in their household had used nonviolent discipline, psychological aggression, and physical violence toward the target child and whether they believed that using corporal punishment is necessary. Logistic regression analyses supported the hypothesis that children with disabilities are treated more harshly than children without disabilities. The findings suggest that policies and interventions are needed to work toward the United Nations’ goals of ensuring that children with disabilities are protected from abuse and violence.